Osteoma of left Temporal Bone - A Rare Case Report - Dr Gurumani Sriraman,Dr Deepthi E, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Osteoma is a benign, slow-growing tumour that develops from mature lamellarbone tissue. It is a single pedunculate mass which often happens unilaterally. The externalauditory canal is more frequently affected by osteomas than other parts of the temporal bone. The purpose of this case report is to review this rare mastoid osteoma and discuss differential diagnosis and treatment